FILSAFAT TEKNOLOGI INFORMASI DAN PATTERN RECOGNITION SECARA ETIMOLOGIS - Rahmad Fauzi; Ilham Sahdi Lubis; Ahmad Zainy (JURNAL MathEdu (Mathematic Education Journal), 2023)
The philosophy of information technology is a field that studies the philosophy Information technology includes the use of systems and tools related to the processing, storage, and communication of information, including computers, the internet, and software. Philosophy of science is a branch of philosophy that studies the principles, foundations, and methods that underlie science and scientific practice, The method used in this research is the literature method, Data collection in literature studies involves a combination of qualitative methods, such as text analysis, context studies, and interviews, which enable researchers to develop a rich and in-depth understanding of literary texts and the aspects associated with them.